Behavioral Predictors of Outpatient Mental Health Service Utilization Within 6 Months After Traumatic Brain Injury in Adolescents. Issue 12 (22nd August 2013) - Kurowski, Brad G.; Wade, Shari L.; Kirkwood, Michael W.; Brown, Tanya M.; Stancin, Terry; Taylor, H. Gerry
Abstract : Objectives: To characterize utilization of mental health services and determine the ability of a behavior problem and clinical functioning assessment to predict utilization of such services within the first 6 months after moderate and severe traumatic brain injury in a large cohort of adolescents. Design: Multicenter cross‐sectional study. Setting: Outpatient setting of 4 tertiary pediatric hospitals, 2 tertiary general medical centers, and 1 specialized children's hospital. Participants: Adolescents age 12‐17 years (n = 132), 1‐6 months after moderate‐to‐severe traumatic brain injury. Methods: Logistic regression was used to determine the association of mental health service utilization with clinical functioning as assessed by the Child and Adolescent Functional Assessment Scale and behavior problems assessed by the Child Behavioral Checklist. Main Outcome Measurement: Mental health service utilization measured by the Service Assessment for Children and Adolescents. Results: Behavioral or functional impairment occurred in 37%‐56%. Of the total study population, 24.2% reported receiving outpatient mental health services, 8.3% reported receiving school services, and 28.8% reported receiving any type of mental health service. Use of any (school or outpatient) mental health service was associated with borderline to impaired total Child and Adolescent Functional Assessment Scale (odds ratio 3.50 [95% confidence interval, 1.46‐8.40]; P < .01) and the Child Behavioral Checklist Total Competence (odds ratio 5.08 [95% confidence interval, 2.02‐12.76]; P < .01). Conclusions: A large proportion of participants had unmet mental health needs. Both the Child and Adolescent Functional Assessment Scale and the Child Behavioral Checklist identified individuals who would likely benefit from mental health services in outpatient or school settings. Future research should focus on methods to ensure early identification by health care providers of adolescents with traumatic brain injury in need of mental health services.